Implementación de un sistema de inventario para la gestión en la mercancía de la tienda de regalos Maffra en la ciudad de Duitama (2023)
Managing an inventory system and carrying out proper control over it, is what leads organizations to have a correct balance in what is needed and what is not, good inventory management of a company is necessary for strengthening and growth of it's on the market.